Pengaruh Stres Kerja, Keselamatan Kerja Dan Kesehatan Kerja Terhadap Kinerja Karyawan (Pada PT. Etta Indotama Yogyakarta) - Ulvia Rahimah; Hadi Sunaryo; Pardiman Pardiman (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThis study aims to determine the effect of work stress, occupational safety and health on employee performance at PT. Etta Indotama Yogyakarta. The sample used in this study were 80 production employees. The data analysis method used in this research is quantitative data analysis using multiple linear regression analysis. The data testing used is simultaneous hypothesis testing (F) and partial hypothesis testing (t). The results showed that simultaneously the independent variable had a significant effect on the dependent viable. Based on the partial test results, the variables work stress, occupational safety and health have a significant effect on the performance of the employees of PT Etta Indotama Yogyakarta. Keywords: Job Stress, Work Safety, Occupational Health and Employee Performance